Sistem Pakar Diagnosa Kerusakan Komputer Dengan Metode Case Based Reasoning Pada Toko Click Komputer Karawang - Edy Widodo; Anisa Devi Asmara (DPPM Universitas Pelita Bangsa, 2025)
Computer technicians often require a significant amount of time to diagnose computer damage, and in many cases, the process is delayed while they determine the appropriate solution. To address this issue, an expert system can be developed to provide faster and more accurate diagnoses of computer problems. This study applies the Case Based Reasoning (CBR) method, an artificial intelligence approach that solves new problems by referring to solutions from previous similar cases. By comparing current symptoms with stored cases in the system, appropriate recommendations can be generated efficiently. The system is developed using the PHP programming language, while MySQL is utilized as the database for storing case data and solutions. Through this implementation, the expert system is expected to assist technicians in identifying types of computer damage quickly, precisely, and accurately. As a result, it can reduce diagnostic time, improve work efficiency, and support technicians in delivering proper handling and effective solutions for computer-related issues.